Pengaruh Keragaman Produk Dan Promosi Terhadap Keputusan Pembelian Pada CV. Jati Mulia Kauman Tulungagung - Wilona Gatra Wedari; Deby Santyo Rusandy; Anita Sumelvia Dewi (Journal of Management and Social Sciences, 2023)
The development and advancement of technology in the modern era has had a tremendous impact on efforts to create superiority in competition between companies. So companies are required to continue to improve their competitiveness so that they are not inferior to other companies. This research aims to determine and explain the results of the influence of product diversity and promotions on purchasing decisions at CV. Jati Mulia Kauman Tulungagung. The method used is quantitative descriptive. The sample for this research is consumers who have made purchases at CV. Jati Mulia Kauman Tulungagung as many as 50 consumers. The sampling technique uses accidental sampling. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is classic assumptions, multiple linear regression. The results of this research are that there is a positive and significant influence of product diversity on purchasing decisions with a significant value of 0.004 < 0.05. There is a positive and significant influence of promotion on purchasing decisions with a significant value of 0.000 <0.05. There is a simultaneous influence of product diversity and promotion on purchasing decisions with a significant value of 0.000 <0.05.